2020
DOI: 10.14720/aas.2020.116.1.1181
|View full text |Cite
|
Sign up to set email alerts
|

Genetic studies of soybean [Glycine max (L.) Merr.] response to seed storage stress factors

Abstract: <p>Soybean [<em>Glycine max</em> (L.) Merr.] responded differently to storage stress factors. This research work aimed at assessing genetic potentials of fifteen soybean varieties to storage stress via accelerated aging technique and grouping them based on their levels of tolerance to storage stress using simple sequence repeat (SSR). Tolerance of the seed of 15 soybean varieties to storage stress was assessed by subjecting them to accelerated aging for 0, 6, 12, and 24 hours at 42 °C tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Kapoor et al (2010) has reported that varieties of chickpea responded differently with reference to physiological and biochemical changes occurring due to seed ageing. Similarly, Okunlola et al, (2020) attributed significant variation in germination and other seedling vigor parameters recorded under artificial aging treatments to different genetic makeup of the soybean varieties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kapoor et al (2010) has reported that varieties of chickpea responded differently with reference to physiological and biochemical changes occurring due to seed ageing. Similarly, Okunlola et al, (2020) attributed significant variation in germination and other seedling vigor parameters recorded under artificial aging treatments to different genetic makeup of the soybean varieties.…”
Section: Discussionmentioning
confidence: 99%
“…(Akande et al, 2012) where Nx is the number of normal seedlings that emerged on day x after seeding and DAP is days after planting Germination Rate Index (GRI) This reflects the percentage of germination on each day of the germination period and was calculated as follows: Esechi, 1994) where, G = germination on each day after seed placement 1, 2, x = corresponding day of germination Seedling vigour Index (SVI) The estimation of the seedling vigour index, involved the measurement of seedling length of five randomly selected seedlings of each replicate from the soil level at 8 and 14 days after planting. The SVI was then calculated as follows: SVI = " % $ * #++ (Adetumbi et al, 2019) Accelerated ageing procedure with corresponding germination and vigor test Clean seeds of the twelve genotypes were selected and subjected to accelerated ageing using a modified procedure of Ghosh et al (2013) and Okunlola et al (2020). A hundred seeds in three replicates of each genotype was counted and placed in an improvised plastic ageing box (11.0 × 11.0 × 3.5 cm), ensuring the seeds form a single layer.…”
Section: Seed Vigour Assessmentmentioning
confidence: 99%
“…To validate the extent of genetic variability in germplasm, some scientists have used many statistical techniques, among which are principal components (PCA) and cluster analyses. PCA and cluster analyses are statistical methods for the characterization of germplasm based on their origins, genetic constitutions, and contributions of traits to the total variations (Ogunbodede, 1997;Akinyosoye et al, 2017;Okunlola et al, 2020). PCA and cluster analyses have been used to determine the extent of phenotypic variability in germplasm collections, namely maize, mungbean, pea, soybean, alfalfa, and AYB, among others (Matus et al, 1999;Akinyosoye et al, 2017;Okunlola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PCA and cluster analyses are statistical methods for the characterization of germplasm based on their origins, genetic constitutions, and contributions of traits to the total variations (Ogunbodede, 1997;Akinyosoye et al, 2017;Okunlola et al, 2020). PCA and cluster analyses have been used to determine the extent of phenotypic variability in germplasm collections, namely maize, mungbean, pea, soybean, alfalfa, and AYB, among others (Matus et al, 1999;Akinyosoye et al, 2017;Okunlola et al, 2020). Also, understanding the relationships among important traits is very useful in indirect selection (Kumar et al, 2015;Sesay et al, 2017).…”
Section: Introductionmentioning
confidence: 99%